Navigating WTP disparities: a study of tourist and resident perspectives on coastal management - Onofrio, Fabiola; Rodella, Ilaria; Gilli, Marianna (Frontiers in Environmental Economics, 2025)
Coastal areas are increasingly exposed to environmental pressures due to mass tourism and climate change. Understanding how different user groups value coastal environmental services is essential to design effective and sustainable management strategies. This study explores differences in willingness to pay (WTP) for key coastal services-cleanliness, security, and environmental protection-between tourists and residents in two highly touristic Italian regions: Marche and Campania. Data were collected through a structured survey administered to beach users in both regions. Findings indicate that tourists are more willing to financially support initiatives related to environmental protection, while residents prioritize corrective actions aimed at mitigating the negative impacts of tourism. These preferences reflect differing perceptions and expectations regarding coastal management. The results underline the importance of tailoring coastal policies to specific stakeholder groups. Tools such as environmental tourism taxes and differentiated communication strategies could improve resource allocation, enhance stakeholder engagement, and increase the effectiveness of coastal management initiatives.